The benefits of vocational education and training - (:unkn) unknown (Publications Office of the European Union, 2011)
"This European research review of the benefits of vocational education and training (VET) is released at a time when Europe is taking stock of the progress achieved in the Lisbon process and has launched a new strategy to promote growth and enable swift recovery from the economic crisis. Research on the benefits of education has a long history in the economics of education, but the same cannot be said about research on the specific benefits of VET. For VET policy-making, however, it is crucial that decisions on actions and measures are adequately supported by sound research evidence. This research review gathers and analyses evidence on the economic and social benefits of VET from across Europe at different levels. The overall impression is that VET research and VET policy are not yet structurally connected in Europe." (Hrsg., BIBB-Doku)
Keywords: S 4.3.3 Effizienz & Effektivität des Berufsbildungswesens; G 1.3.3.1 Qualifikationsverwertung; I 2.2 Europa; Berufsbildung; Kosten-Nutzen-Analyse; Qualifikationsverwertung; Ökonomische Faktoren; Soziale Faktoren; Europa